Is syphilis infection a risk factor for cervicovaginal HPV occurrence? A case-control study - Napoleão Moura Dias Neto; Vanessa Gonçalves Nunes Moura Dias; Denise Maria Christofolini (Elsevier, 2024)
Background: Syphilis and human papillomavirus (HPV) are sexually transmitted infections affecting women in the same risk group. Thus, the main objective of the present study was to investigate the prevalence of HPV in a population of women with and without syphilis and observe the characteristics of HPV cervical lesions when coinfection occurs. Sociodemographic factors associated with coinfection were also evaluated. Methods: This case-control study was conducted at a Brazilian HIV/STD testing and training center. Study groups were composed of women with (case) and without syphilis (control), paired by age. The presence of HPV, HPV subtype, and lesion severity were investigated. All women were subjected to a sociodemographic interview, clinical data collection, cell collection for cytopathological analysis, and a hybrid capture test for HPV diagnosis. The chi-square test was used for statistical analysis. Results: The sample consisted of 176 women, 88 in each group. The prevalence of HPV was 14.8 % in the case (n = 13) and 18.1 % in the control group (n = 16), and there was no statistically significant difference between them. Illiterate individuals were more prevalent in the control group (p = 0.023). Considering women with suggestive signs of STIs, 30 % (6) of the patients and controls had high-risk HPV, and 15 % (3) had coinfection. The cytopathological assessment showed no differences between the groups concerning cellular atypia. However, ASC-US and ASC-H (atypical squamous cells of undetermined significance and high-grade) were only found in women with coinfections, with 75 % of these patients testing positive for high-risk HPV. Considering the distribution of lesions on the cervix, the HSIL (high-grade intraepithelial lesion) was assessed in high-risk HPV patients, both cases and controls. Conclusions: The prevalence of HPV was not increased in patients infected with syphilis. In addition, coinfection does not seem to be an aggravating factor for the presence of precursor lesions of cervical cancer.